COVID-19 Resulted in Reduction Trainee Bedside Experience, But No Reduction in Surgical Experience - Itay Ron, B.Sc.; Cynthia Kyin, B.Sc.; David Shaked Zari, B.Sc.; Bezalel Peskin, M.D.; Nabil Ghrayeb, M.D.; Doron Norman, M.D.; Jacob Shapira, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2024)
Purpose: Because of the concerns regarding residency process during the pandemic, this study aimed to investigate the volume of clinical interactions of orthopaedic residents at a tertiary hospital by reporting the number of patients treated in the outpatient clinic, inpatient ward, and operating room. Methods: This retrospective chart study evaluated variables such as volume of clinical interactions of orthopaedic residents at a tertiary hospital by reporting the number of patients treated in the outpatient clinic, inpatient ward, and operating room, from an orthopaedic department in a tertiary trauma center throughout the COVID-19 pandemic era. Comparing these measures was an indirect evaluation tool for measuring the amount of work completed and clinical exposure gained by the residents. Results: Occupancy percentage, hospitalization days, admissions to the department, and attendance of the outpatient clinic were all decreased during the pandemic. No significant changes were evident in the total number of surgeries nor the number of elective surgeries during the pandemic. Conclusions: Overall, a reduction in overall hospitalization days, admissions to the department, total number of visits in the outpatient clinic, and occupancy percentage of the ward was observed during COVID-19. However, there was no difference in the average number of monthly surgeries between the pre-COVID-19 and COVID-19 timeframes. Level of Evidence: Level III, retrospective comparative review.